Long-Term Comparison of Single-Level Bryan and ProDisc-C Cervical Disc Arthroplasty: A Minimum 10-year Follow-Up of Clinical and Radiographic Outcomes - Dacheng Sang; Zhenxu Li; Xueshi Tian; Ruomu Qu; Shuyang Li; Xiaoxiong Yang; Lisheng Hu; Yanbin Zhao; Yu Sun; Feifei Zhou (Global Spine Journal, 2026)
Study Design Retrospective cohort study. Objective To compare long-term clinical and radiographic outcomes between the Bryan and ProDisc-C cervical disc prostheses following single-level cervical disc arthroplasty (CDA), with particular focus on sagittal alignment, motion behavior, heterotopic ossification (HO), and radiographic adjacent segment degeneration. Methods This retrospective single-center cohort study included patients who underwent single-level CDA with either the Bryan or ProDisc-C prosthesis between 2004 and 2014 and had complete minimum 10-year clinical and radiographic follow-up data. Clinical outcomes were evaluated using the Neck Disability Index (NDI), visual analog scale for neck and arm pain, and modified Japanese Orthopaedic Association (mJOA) score. Radiographic assessments included cervical lordosis, segmental and total range of motion (ROM), functional spinal unit (FSU) height, cervical sagittal vertical axis, T1 slope, HO according to the McAfee classification, and radiographic adjacent segment degeneration assessed using the Walraevens scoring system. Results A total of 71 patients were included, including 40 treated with the Bryan prosthesis and 31 treated with ProDisc-C. The median follow-up duration was 141 months [IQR, 123–173 months]. Both groups demonstrated significant improvements in VAS-N, VAS-A, NDI, and mJOA scores compared with preoperative baseline values, with no significant between-group differences at final follow-up. Radiographically, final index-level ROM was comparable between groups, although a within-group reduction from baseline was observed in the Bryan group. ProDisc-C was associated with greater index-level lordosis and higher measured FSU height at final follow-up. The incidence of radiographic adjacent segment degeneration was comparable between the Bryan and ProDisc-C groups. HO was more frequent in the ProDisc-C group, with differences in HO grade and distribution between the two prostheses. Revision rates were comparable between groups. Conclusion At a minimum 10-year follow-up, Bryan and ProDisc-C CDA provided durable and comparable clinical outcomes after single-level surgery. Direct between-group comparisons showed differences in selected radiographic parameters, including index-level lordosis, measured FSU height, and HO characteristics, whereas final index-level ROM and radiographic adjacent segment degeneration were comparable. These findings suggest that implant-related radiographic differences may exist, but they did not translate into measurable differences in long-term clinical outcomes in this cohort.